Efficacy of Modified Huangqi Chifeng decoction in alleviating renal fibrosis in rats with IgA nephropathy by inhibiting the TGF-β1/Smad3 signaling pathway through exosome regulation. (1st March 2022) - Zhao, Mingming; Yang, Bin; Li, Liusheng; Si, Yuan; Chang, Meiying; Ma, Sijia; Li, Ronghai; Wang, Yuejun; Zhang, Yu
Abstract: Ethnopharmacological relevance: IgA nephropathy is the most common form of primary glomerulonephritis and is a major cause of renal failure worldwide. Modified Huangqi Chifeng decoction (MHCD), a traditional Chinese herbal preparation, has clinical efficacy in reducing the 24-h urine protein levels in patients with IgA nephropathy. However, the molecular mechanism of MHCD needs further study. Aim of the study: This study aimed to investigate the mechanisms by which MHCD treatment alleviates renal fibrosis. Materials and methods: An IgA nephropathy rat model was established using bovine serum albumin, carbon tetrachloride, and lipopolysaccharide. The rats were divided into control, model, telmisartan, low-dose MHCD, medium-dose MHCD, and high-dose MHCD groups. Treatments were administered to these groups for 8 weeks. Subsequently, the 24-h urine protein, serum creatinine, blood urea nitrogen, and blood albumin levels were measured. Pathological changes and degree of fibrosis in renal tissues were observed, and levels of the transforming growth factor-β1 (TGF-β1)/Smad3 signaling pathway components in renal tissues and TGF-β1 in urinary exosomes were measured. Results: Telmisartan and MHCD reduced 24-h urine protein levels, alleviated renal pathological injury, and decreased the renal expression of fibronectin, laminin, and collagen IV in rats with IgA nephropathy. Urinary exosomes were extracted and identified for further investigation of their role in renal fibrosis. MHCD reduced TGF-β1 expression in urinary exosomes and reduced TGF-β1 and p-Smad3 levels in renal tissues. Conclusion: MHCD alleviated renal fibrosis in rats with IgA nephropathy by inhibiting the TGF-β1/Smad3 signaling pathway through the downregulation of TGF-β1 expression in exosomes. Graphical abstract: Image 1 Highlights: MHCD could improve renal function in rats with IgA nephropathy. Its mechanism involved the regulation of TGF-β1/Smad3 signaling pathway by exosomes. MHCD may be a potential Chinese herbal preparation for alleviating IgA nephropathy.